Sexual Knowledge and Sexual Attitudes towards Premarital Sexual Intentions of High School Adolescents - Petrus Aprilianto Lima Kolin; M. K. P. Abdi Keraf; R. Pasifikus Christa Wijaya; Indra Yohanes Kiling (Journal of Health and Behavioral Science, 2021)
Abstract: Adolescence is a transition period between childhood and adulthood. Young people are usually very curious. This study aims to determine whether sexual knowledge and attitudes are related to premarital sexual intentions among teenagers in Kupang City. This study uses a type of quantitative sample research using probability sampling methods. This study was conducted on high school youth in Kupang City with a total population of 3351 people with a sample of 283 subjects. The measurement used a modified knowledge scale from Reinisch, J (1990), attitude to behavior scale using the adaptation scale from Adhikara (2017), and the sexual intention scale using the adaptation scale from planned behavior theory tested by YSI-Q (2017). Data analysis using the Spearman correlation technique. Based on the results of the research data analysis, it was found that sexual intentions are not related to sexual knowledge but that sexual intentions are related to attitudes towards behavior. Abstrak: Masa remaja merupakan masa transisi antara masa kanak-kanak dan masa dewasa. Remaja umumnya memiliki rasa ingin tahu yang tinggi. Penelitian ini bertujuan untuk mengetahui apakah pengetahuan seksual dan sikap seksual berhubungan terhadap niat seksual pranikah pada remaja SMA di Kota Kupang. Penelitian ini menggunakan jenis penelitian kuantitatif dengan pemgambilan sampel menggunakan metode probability sampling. Penelitian ini dilakukan pada remaja SMA di Kota Kupang dengan populasi dengan total 3351 dengan sampel penelitian sebanyak 283 subjek. Pengukuran menggunakan skala pengetahuan yang dimodifikasi dari Reinisch, J (1990), skala sikap terhadap perilaku menggunakan skala adaptasi dari Adhikara (2017) dan skala niat seksual menggunakan skala adaptasi dari theory planned behavior yang diuji coba oleh YSI-Q (2017). Analisis data menggunakan teknik korelasi spearman. Berdasarkan hasil analisi data penelitian, diperoleh bahwa niat seksual tidak berhubungan dengan pengetahuan seksual tetapi niat seksual berhubungan dengan sikap terhadap perilaku